2020
DOI: 10.1177/2332858420969691
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Just the Average Effect: Variation in Head Start Treatment Effects on Parenting Behavior

Abstract: Parent engagement has been a cornerstone of Head Start since its inception in 1965. Prior studies have found evidence for small to moderate impacts of Head Start on parenting behaviors but have not considered the possibility that individual Head Start programs might vary meaningfully in their effectiveness at improving parenting outcomes. The present study uses the Head Start Impact Study to examine the average effect of random assignment to and participation in Head Start on parenting outcomes as well as vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Research on the effects of Head Start on fathering is far more limited. Although a number of studies have exploited variation between Head Start sites to examine the effects of demonstration projects on father involvement (Fagan & Iglesias, 1999;Fagan & Stevenson, 2002;McAllister et al, 2004;Padilla, 2020;Raikes et al, 2002Raikes et al, , 2005Raikes & Bellotti, 2006), these studies focused primarily on resident fathers or did not identify fathers' residential status.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research on the effects of Head Start on fathering is far more limited. Although a number of studies have exploited variation between Head Start sites to examine the effects of demonstration projects on father involvement (Fagan & Iglesias, 1999;Fagan & Stevenson, 2002;McAllister et al, 2004;Padilla, 2020;Raikes et al, 2002Raikes et al, , 2005Raikes & Bellotti, 2006), these studies focused primarily on resident fathers or did not identify fathers' residential status.…”
Section: Prior Literaturementioning
confidence: 99%
“…Head Start serves nearly 1 million children annually, one-third of all poor children in the United States aged between 3 and 5 (Child Trends Data Bank, 2015), and more than half of these children have a nonresident father (Hulsey et al, 2011). Although a number of studies have found that Head Start increases and improves mothers' Gelber & Isen, 2013;Zhai et al, 2013) and resident parents' (Padilla, 2020) engagement with children, little is known about its effects on father involvement, particularly among nonresident fathers.…”
Section: Introductionmentioning
confidence: 99%